Besinning oor die twee ryke-leer - Wyk, J. H. van (Hervormde teologiese studies, 1988)
Reflections on the theory of the two kingdoms The question concerning the so-called two kingdoms, the kingdom of God/heaven and the kingdom of the devil/earth is as old as the history of humanity itself. Does not Christ himself refer to what belongs to Ceasar and what belongs to God (Matt 22: 21)? In this article the author first of all tries to summarise the six great theological models, with modifications, and thereafter briefly researches the South African context. He comes to the conclusion that there is only one King, one kingdom, one Word and one life; distinctions may be drawn but divisions are confusing.